The 'technological take-off' and the 'critical mass'. A trial conceptualization - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2015)
Similar to economic growth, the process of technology diffusion may well be approximated by easily distinguishable phases (stages). During the initial phase, the process of diffusion slows, whereas subsequently, under favourable circumstances, it accelerates and proceeds at an exponential growth rate, ultimately approaching relative stabilisation (maturity) when the growth rates gradually diminish. Following the proposed by Rostow (1956) conceptualization of the 'take-off', this work is a trial conceptualization of the concepts related to the technology diffusion process, namely – 'technological take-off' and the 'critical mass'. It demonstrates the 'step-by-step' procedure of the identification of the 'critical mass', and the interval when the 'technological take-off' emerges. We propose the term 'technological take-off' and define it the time interval when the nature of the diffusion process is radically transformed due to shifting the rate of diffusion and forcing the transition from condition of stagnation into dynamic and self-sustaining growth (diffusion) of new technology; while the 'critical penetration rate' we define as the threshold that, once passed, provokes the diffusion to become self-perpetuating.
Keywords: O3; 330; technology; technology diffusion; critical mass; take-off